Microgreen farming A new approach for nutrient rich greenfood for remote locations - Rani, Seema; Singh2, Narendra; Maurya, S B; Phour, Manisha (Indian Farming, 2019)
Microgreen production is a newfangled approach in green farming in which fresh green vegetableplants in tiny form i.e. 10-15 cm height are cultivated. These plants are consumed raw afterharvesting without root, within 10-12 days of sowing. In this approach, certain vegetables seedsare grown in small plastic trays in soilless organic media. The trays are kept inside the minimodulargreenhouse in tier system to utilize the vertical space and to maintain the suitableenvironmental conditions for growing the plants. These small fresh green plants are rich source ofnecessary minerals, vitamins and other beneficial phyto-bioactive compounds for health than theircounterpart. Self-growing and eating these small green plants can help to manage societal sicknessand monotonous state of mind which are quite common in remote locations. Growing thesenutritious plants is economical because the study conducted on different vegetable microgreensrevealed that an average of 40-50 g yield/tray can be achieved with an average cost of seeds` 6.30/tray. The vegetables like broccoli, red cabbage etc. have more expenditure i.e. about` 32.0/tray as their seeds are costly but vegetables like pink radish, white radish, cabbage,cauliflower, turnip etc. have very low seed cost i.e. about ` 0.4 to 1.96/tray.